2018
DOI: 10.31788/rjc.2018.1122092
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Atmospheric Pressure Plasma Treated Polyester Fabrics

Abstract: Polyester fabrics are treated in low-temperature plasma. Plasma-treated fabrics displayed a substantial variation in the surface structure. Plasma treated fabrics are grafted by using maleic acid (Mac). X-ray diffraction patterns are used to estimate crystallinity of polyester fabrics. From FTIR studies, it is observed that (-OH) group is induced in case of grafted polyester fabric that enhanced the wettability of the fabric. The enhancement of dye uptake in polyester fabrics was evaluated with the help of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Thus, this rough surface led to more physical loosening of the microstructure of the fabric. Furthermore, X-ray diffraction measurements [ 11 , 31 ] also showed that the crystallinity of polyester fabrics was reduced by DBD plasma treatment. Dave et al [ 9 ] used the FTIR spectrum to show the amorphization of polyester fabrics by DBD plasma treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this rough surface led to more physical loosening of the microstructure of the fabric. Furthermore, X-ray diffraction measurements [ 11 , 31 ] also showed that the crystallinity of polyester fabrics was reduced by DBD plasma treatment. Dave et al [ 9 ] used the FTIR spectrum to show the amorphization of polyester fabrics by DBD plasma treatment.…”
Section: Resultsmentioning
confidence: 99%
“…During etching reaction, weight loss of the substrate occurs, and the topmost layer of the substrate is stripped off [ 16 ]. Moreover, the microstructure of polyester fiber has also been changed, and under the effect of DBD plasma, the fiber crystallinity has been reduced [ 9 , 11 , 31 ]. As a result, the fibrous structure can become looser and more porous.…”
Section: Discussionmentioning
confidence: 99%